Cutting Speed Analysis of Organic Waste Chopping Machine Fly Wheel Model Level Control - I Putu Darmawa; I Nengah Ludra Antara; I Nyoman Sutarna; Ida Bagus Puspa Indra; I Nyoman Gunung (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
This machine is used to chop leaves, twigs and branches into very small pieces, to avoid the bad smell due to the decay of organic waste and can be used as compost. The amount of cutting speed on the organic waste chopping machine with a chopping time of 2.5 kg of ketapang leaves is the average time obtained without fly wheels 2.0 minutes and with fly wheels 1.7 minutes, a time difference of 0.3 minutes. The chopping time of 2.5 kg of ketapang branches with an average time obtained without a fly wheel of 2.2 minutes and with a fly wheel of 2.0 minutes, a time difference of 0.2 minutes. The chopping time of teak branches is 2.5 kg with an average time obtained without a fly wheel of 2.6 minutes and with a fly wheel of 2.0 minutes, so the time difference is 0.6 minutes. So the cutting speed using a fly wheel is better. The results of the productivity obtained on the organic waste chopping machine, for the results of leaf chopping productivity without a fly wheel of 48% and those using a fly wheel of 58%, and the results of leaf chopping with a fly wheel are 10% more productive, for the productivity of chopping twigs without a fly wheel of 44% and those using a fly wheel of 49%, so the results of chopping twigs with a fly wheel are 5% more productive, and the results of chopping branches without a fly wheel of 37% and those using a fly wheel of 49%, so the results of chopping branches with a fly wheel are 12% more productive.